Analysis of The Impact of Using QRIS Merchant on Efficiency and Safety at UMKM in Manahan Shelter - Khoirunnisa, Triya Isma; Abidin, Ali Zainal (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
All social activities, including payment systems, are experiencing rapid changes due to digitalization and technological advances. Bank Indonesia and the Indonesian Payment System Association (ASPI) launched an innovation, QRIS, as a QR Code-based non-cash payment standard. QRIS provides many benefits, especially for MSME players, who play a crucial role in maintaining the stability of the Indonesian economy. This study aimed to determine the effect of convenience, safety, and user attitudes on decisions to use QRIS. The population in this study was 210 shelters located in Manahan. This study uses a purposive technique with a sample size of 20% of the counters using QRIS as a payment method. This research uses a descriptive qualitative approach, for the primary data was obtained directly by distributing questionnaires and interviews to MSME owners in Manahan shelters. After that, the data obtained is processed using the interactive data analysis method by testing data reduction analysis, data display, and conclusion. The results of this study indicate that using the QRIS payment method makes it easier for consumers and MSME owners in Manahan shelters. Using QRIS as a means of payment does not guarantee safety even though it is equipped with an international standard safety system. However, technical disturbances often occur, which cause transfer failures. The solution so that technical disturbances do not occur when using QRIS is to check the internet network first.